2020
DOI: 10.1371/journal.pone.0244572
|View full text |Cite
|
Sign up to set email alerts
|

HIV treatment cascade among people who inject drugs in Ukraine

Abstract: The HIV treatment cascade is an effective tool to track progress and gaps in the HIV response among key populations. People who inject drugs (PWID) remain the most affected key population in Ukraine with HIV prevalence of 22% in 2015. We performed secondary analysis of the 2017 Integrated Bio-Behavioral Surveillance (IBBS) survey data to construct the HIV treatment cascade for PWID and identify correlates of each indicator achievement. The biggest gap in the cascade was found in the first “90”, HIV status awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…10 These groups have been identified as facing challenges to diagnosis, treatment, and remaining in care. 11,12 Other key populations also face challenges with high numbers of undiagnosed HIV, high HIV prevalence, less ART initiation, and low rates of viral suppression. 13 In addition to low ART rollout, the uncontrolled HIV epidemic is also driven by a notable prevention gap.…”
Section: Introductionmentioning
confidence: 99%
“…10 These groups have been identified as facing challenges to diagnosis, treatment, and remaining in care. 11,12 Other key populations also face challenges with high numbers of undiagnosed HIV, high HIV prevalence, less ART initiation, and low rates of viral suppression. 13 In addition to low ART rollout, the uncontrolled HIV epidemic is also driven by a notable prevention gap.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide diversity between countries with a broad spectrum of political, economic, and HIV epidemic status in reaching 90-90-90 targets among PWID. Comparison the rst cascade indicator in Iran with other countries revealed that this proportion was relatively higher than in Central Asia or other European countriesand some countries like Mexico (7)(8)(9)(10).Regarding the 57% ART coverage among PWID who were aware of their HIV status, we have found that in this study is lower than the average in other Low-Middle income countries globally and within Eastern Europe and Central Asia (7,11). The level of viral load suppression in Iranian PWID is not comparable and desirable compared to other countries globally which is reported about three quarters of all HIV-infected PWID on ART (7).…”
Section: Discussionmentioning
confidence: 96%
“…This effect may be explained by the lack of motivation to engage in care, 25 the role of stigma and discrimination in deterring optimal care, 26,27 or other structural barriers. 28,29…”
Section: Discussionmentioning
confidence: 99%
“…This effect may be explained by the lack of motivation to engage in care, 25 the role of stigma and discrimination in deterring optimal care, 26,27 or other structural barriers. 28,29 Substance use, especially IDU, is known to decrease the chance of VS 30 because of adherence issues 31 and through other pathways. We observed this association in bivariate analyses, as expected.…”
Section: Discussionmentioning
confidence: 99%